PENATAAN PURA KERTASARI DESA PAKRAMAN PERASI, DESA PERTIMA KECAMATAN KARANGASEM KABUPATEN KARANGSEM - N.M. Swanendri; I.N Susanta (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
Pura Kerta Sari (Kerta Sari temple) is one of temples located in Desa Pakraman Perasi, Karangasem (Perasivillage). Its existence is not only linked to the community of Perasi village, but also outside of the village.Nowadays, physical condition of the temple is moderate, but some parts have a condition that are quitealarming, i.e. : barrier wall collapsed, less structured and less organized in worship area and bad accesscondition. These circumstances will not only interfere with the implementation of religious activities, but alsosustainability and sanctity of the temple building. It has encouraged the committee (pengempon and prajuru)to conduct a planning activity (building and environmental improvements) assisted by Community ServicesTeam of Architecture department UNUD that lasted from March - November 2016. Through a series ofprocesses (data collection, discussion, ideas presentation etc.), it was decided that building andenvironmental improvements of Pura Kerta Sari will be included access improvement, reinforce templeboundary area and its barrier wall, repair and rebuilding shrine buildings that includes palinggih padmasari,palinggih anglurah, palinggih apit lawang, tahaban banten, bale pesandekan and bale sakenem.